Multiple Novel Clades of Anopheline Mosquitoes Caught Outdoors in Northern Zambia - Jones, Christine M.; Ciubotariu, Ilinca I.; Muleba, Mbanga; Lupiya, James; Mbewe, David; Simubali, Limonty; Mudenda, Twig; Gebhardt, Mary E.; Carpi, Giovanna; Malcolm, Ashley N.; Kosinski, Kyle J.; Romero-Weaver, Ana L.; et al. (Frontiers in Tropical Diseases, 2021)
Residual vector populations that do not come in contact with the most frequently utilized indoor-directed interventions present major challenges to global malaria eradication. Many of these residual populations are mosquito species about which little is known. As part of a study to assess the threat of outdoor exposure to malaria mosquitoes within the Southern and Central Africa International Centers of Excellence for Malaria Research, foraging female anophelines were collected outside households in Nchelenge District, northern Zambia. These anophelines proved to be more diverse than had previously been reported in the area. In order to further characterize the anopheline species, sequencing and phylogenetic approaches were utilized. Anopheline mosquitoes were collected from outdoor light traps, morphologically identified, and sent to Johns Hopkins Bloomberg School of Public Health for sequencing. Sanger sequencing from 115 field-derived samples yielded mitochondrial COI sequences, which were aligned with a homologous 488 bp gene segment from known anophelines (n = 140) retrieved from NCBI. Nuclear ITS2 sequences (n = 57) for at least one individual from each unique COI clade were generated and compared against NCBI’s nucleotide BLAST database to provide additional evidence for taxonomical identity and structure. Molecular and morphological data were combined for assignment of species or higher taxonomy. Twelve phylogenetic groups were characterized from the COI and ITS2 sequence data, including the primary vector species Anopheles funestus s.s. and An. gambiae s.s. An unexpectedly large proportion of the field collections were identified as An. coustani and An. sp. 6. Six phylogenetic groups remain unidentified to species-level. Outdoor collections of anopheline mosquitoes in areas frequented by people in Nchelenge, northern Zambia, proved to be extremely diverse. Morphological misidentification and underrepresentation of some anopheline species in sequence databases confound efforts to confirm identity of potential malaria vector species. The large number of unidentified anophelines could compromise the malaria vector surveillance and malaria control efforts not only in northern Zambia but other places where surveillance and control are focused on indoor-foraging and resting anophelines. Therefore, it is critical to continue development of methodologies that allow better identification of these populations and revisiting and cleaning current genomic databases.